An Atypical Case of Apical Hypertrophic Cardiomyopathy: Absence of Giant T Waves in spite of Extreme Apical Wall Hypertrophy. (8th December 2015) - Sanidas, Elias; Bonou, Maria; Anastasiadis, Georgios; Tzanis, Georgios; Barbetseas, John
Abstract : Apical hypertrophic cardiomyopathy is an uncommon variant of hypertrophic cardiomyopathy, with hypertrophy mainly affecting the apex of the left ventricle. We hereby describe a case of an octogenarian female patient who was randomly diagnosed with AHCM due to other comorbidities.